Grouping analysis obtained with the indicate relationship of human development and tax charges of the cities of Paraiba state, between 2010 and 2018 (Research, Society and Development, 2020)
For a long period of time in our country, it has been questioned the high value charged in taxes. This questioning brings to light the real efficiency of these mandatory government policies offered to the community and funded out of taxation. Such social public policies are a responsibility of the Brazilian State and will be addressed as a priority the ones that alter social order in relation to factors of longevity, population income, education, social security, foresight, cheers, social assistance, culture and sport. This research has as its main objective to perform an analysis between tax burden and the Human Development Index in Paraiban municipalities, as well as identify equity between several economical and local political factors, showing a possible counterpoint to the criteria already in use for the analysis the volume of the tax burden based on a comparison of the volume of the Gross Domestic Product (GDP) presented in the Report on the “Result of the National Treasury” released by the Ministry of Finance. The current criterion considers only the economic aspects of the tax burden and disregards the existing relationship between public government actions and their effectiveness provided by these tax contributions from the population.